التَّعَامُل مع الحَمَوَيْن في ضَوْءِ سيرة النبي : Dealing with the father-in-law of the spouses in the light of the life of the Messenger, peace and blessings of ALLH be upon him. - Sakr, Mohammed Ebrahim (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
ملخص البحث تعد الأسرة اللبنة الأساسية في بناء المجتمع الإسلامي ، لذلك اهتم الإسلام بتأسيس الأسرة المسلمة القوية ، ووضع لها القواعد التي تحميها وتحافظ عليها ، وكانت سيرة النبي e مثالاً حياً للمحافظة على الأسرة المسلمة ؛ فنجده e مهتماً بأولاده وزوجاته وما يتعلق بهم من نسب ؛ لذلك نجده e يضرب المثل الأعلى في العلاقة مع أقارب الزوجة ومع أزواج بناته ، حتى صارت سيرته e في التعامل مع الحموين مرجعاً أساسياً لكل البشر الذين يبحثون عن الاستقرار الأسري ، وينشدون السعادة الأسرية. لذا كانت تلك الدراسة عن توضيح منهج النبي e في التعامل مع الحموين ؛ أم الزوجة وأبيها ، وكذلك في التعامل مع أزواج بناته ، والهدف من تلك الدراسة الاقتداء بالنبي e في كيفية التعامل مع الحموين ؛ فلقد أحسن إلى حماته أم رومان أم زوجته السيدة عائشة – رضي الله عنها- وكذلك كان باراً بآباء زوجاته ؛ أبي بكر وعمر وأبي سفيان – رضي الله عنهم أجمعين - واهتم النبي e بأزواج بناته ؛ فأحسن إليهم وراعى جانبهم ؛ وذلك لسعادة بناته ؛ وتقوية الصلة بين الأسرتين ؛ وهذا واضح في معاملته – صلى الله عليه وسلم – لعثمان بن عفان وعلي بن أبي طالب وأبي العاص بن الربيع – رضي الله عنهم - أجمعين ، وقد سلكت في هذه البحث المنهج الإستقرائي والمنهج التحليلي ؛ وذلك بتتبع المصادر التي توضح منهج النبي e في التعامل مع الحموين ومع أزواج بناته ، مع تحليل هذه المواقف وأخذ العبرة والعظة منها ، وكان من نتائج هذا البحث حرص النبي e على تقوية الصلة بينه وبين حمويه، وكذلك اهتمامه بأزواج بناته . Abstract The family is the basic building block in building an Islamic society, so Islam took care of establishing a strong Muslim family, and setting rules for it that protects and preserves it. We find that he, may ALLAH’s prayers and peace be upon him, is interested in his children, his wives, and the lineage related to them. Therefore, we find him, may ALLH bless him and grant him peace, setting the ideal in the relationship with the wife's relatives and with the husbands of his daughters, until his biography, may ALLH bless him and grant him peace, in dealing with in-laws became an essential reference for all people who are looking for family stability and seeking family happiness. Therefore, this study was about clarifying the approach of the Prophet, may ALLAH’s prayers and peace be upon him, in dealing with the father-in-law. The wife's mother and father, as well as in dealing with his daughters' husbands. He was kind to his mother-in-law, Umm Ruman, or his wife, Mrs. Aisha - may ALLAH be pleased with her - and he was also kind to the fathers of his wives. Abu Bakr, Omar and Abu Sufyan - may ALLAH be pleased with them all - and the Prophet, may ALLAH’s prayers and peace be upon him, cared for the wives of his daughters; so be kind to them and take care of their side; for the happiness of his daughters; and strengthening the bond between the two families; This is clear in his treatment - may ALLAH bless him and grant him peace - of Othman bin Affan, Ali bin Abi Talib, and Abi Al-Aas bin Al-Rabea - may ALLAH be pleased with them all. In this research, I followed the inductive approach and the analytical approach; This is done by following the sources that explain the approach of the Prophet in dealing with the father-in-law and with the husbands of his daughters, while analyzing these situations and taking the lesson and admonition from them.